An IoT-Based Framework of Digital Payment in Electronic Health Record System -DP-EHR - Yogita Chauhan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Objective- The objective presented this research is to develop the reliable digital payment system from centralized Electronic Health Record (EHR) system that utilizes the blockchain technology to address the challenges of interoperability in the healthcare sector specially for payment. Method- The research introduced the idea on digital payment in the healthcare sector and observed that payment can be facilitated using a Digital payment system and patient history can be centralized using supporting mobile apps and API’s. Additionally the use of an IoT-based approach for payment using digital paper and pen, makes the payment cost-effective. A comprehensive analysis is conducted of existing literature regarding the adoption of blockchain technology in healthcare systems, with a focus on its implementation within Electronic Health Record (EHR) systems. During analysis it is found that the system provide a boom in acceptance of Digital payments, provides Health education and awareness, increase the trend of telemedicine integration. Result- The comprehensive analysis of the literature is based on the adoption of blockchain technology in healthcare systems for digital payments. The research focuses on its implementation within Digital Payment (DP) and Electronic Health Records (EHR). DOI: https://doi.org/10.17762/ijisae.v12i4.6364